Industrial IoT oriented petahertz communication - Nuo HUANG; Weijie LIU; Chen GONG (物联网学报)
Compared with traditional radio frequency communication, petahertz communication (PetaCom) enjoys several distinct advantages including high data rate, low latency and high determinacy, exhibiting essential application potential in industrial internet of things (IIoT).However, IIoT oriented PetaCom suffers issues of link instability and interference in real scenarios.Starting from the basic concepts of IIoT and PetaCom, a comprehensive summary of IIoT oriented PetaCom was presented including channel modeling, physical-layer technologies, user networking, advantages and challenges.The goal is to provide guidance for relevant researches on IIoT oriented PetaCom in the future.